1993
DOI: 10.1172/jci116312
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial beta-adrenergic receptor function during the development of pacing-induced heart failure.

Abstract: The development of pacing-induced heart failure was studied in chronically instrumented, conscious dogs paced at a rate of 240 beats/min for 1 d (n = 6), 1 wk (n = 6), and 3-4 wk (n = 7). Left ventricular (LV) dP/dt was decreased (P < 0.0125) at 1 d, LV end-diastolic pressure and heart rate were increased (P < 0.0125) at I wk, but clinical signs of heart failure were only observed after 3-4 wk of pacing. Plasma norepinephrine rose (P < 0.0125) after 1 d of pacing, whereas LV norepinephrine was reduced (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
3
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(85 citation statements)
references
References 48 publications
2
77
3
2
Order By: Relevance
“…From these data, in contrast to ␤ 1 -ARs, one would not expect a decrease in the expression of cardiac ␤ 2 -ARs in diabetic rats. As a matter of fact, in paced pigs and dogs, ␤ 2 -AR protein and mRNA levels were found to be unchanged despite the reduced number of ␤ 1 -ARs and mRNA content (34,35). Therefore, the decrease that we observed in ␤ 2 -AR protein levels in diabetic rat hearts is somewhat surprising.…”
Section: Discussionmentioning
confidence: 61%
“…From these data, in contrast to ␤ 1 -ARs, one would not expect a decrease in the expression of cardiac ␤ 2 -ARs in diabetic rats. As a matter of fact, in paced pigs and dogs, ␤ 2 -AR protein and mRNA levels were found to be unchanged despite the reduced number of ␤ 1 -ARs and mRNA content (34,35). Therefore, the decrease that we observed in ␤ 2 -AR protein levels in diabetic rat hearts is somewhat surprising.…”
Section: Discussionmentioning
confidence: 61%
“…This may limit increases in ventricular contractility (10). Furthermore, a decreased density of ␤ 1 -receptors has been shown previously in canine pacing-induced failing hearts, which in turn can lead to subsensitivity of ␤-adrenergic pathways and reductions in ␤-agonist-stimulated muscle contractions (4,19,51). Thus the sympathetic pathways the MMR uses in normal conditions are altered in HF, in addition to intrinsic alteration in the myocardial cells and interstitial tissue (myocardial cell death, hypertrophy) (13).…”
Section: Discussionmentioning
confidence: 83%
“…After completion of the control experiments, congestive heart failure was induced via rapid ventricular pacing. This technique has been widely accepted to create chronic model of LV failure and has been utilized by others and us previously (11,12,19,37). Briefly, the right ventricular pacing electrodes were connected to a pacemaker set at 240 beats/min for ϳ30 days, and the experiments were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] As a consequence, depletion of cardiac NE stores and chronic overstimulation of adrenergic receptors leads to worsening of heart failure and sudden death, as well as to profound alterations of postreceptor signal coupling and cardiac remodeling. 6,7 Whereas some studies reported that an impaired NE reuptake was the result of a reduced NET density on cardiac sympathetic nerve endings, 5 other studies demonstrated a loss of sympathetic nerve endings, which occurred mainly in advanced stages of experimental CHF. 8 Likewise, it has been implied that an impaired NE reuptake precedes a loss of sympathetic nerves.…”
mentioning
confidence: 99%